DEVELOPMENT OF MATHEMATICS ANIMATION VIDEOS (MAV) WITH THE QUR'AN CONTEXT ON MATHEMATICAL REASONING ABILITY - Retno Wahyu Arian Sah; Baiduri Baiduri; Siti Inganah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Digital technology can help the learning mathematics process with learning designs in videos by linking mathematical material to the Qur’an context. This is used to help students use mathematical reasoning skills to solve problems and are less interested and enthusiastic when learning, so they can understand the material well and have religious values from the non-Qur'anic text presented. This study aims to create media and learning resources for mathematics in the Qur’an context on mathematical reasoning abilities. The e-module development model used is ADDIE. The data collection instrument uses a validation instrument as a useful data collection tool whether or not the video was developed. Moreover, the practicality instrument is a practicality aspect test given to students after participating in the learning process using the developed product. The study results obtained a score of 3.61 for the material expert and a score of 3.56 for the media expert with the criteria of being tested. The results of student mastery of 82.9% with reasonably practical student responses indicate that the Islamic-based animated video media used is effective and practical. Based on the study's results, the developed media meets the valid, practical, and effective criteria to help develop students' reasoning abilities.